Investigating the effects of lLecithin-PGPR mixture on physical properties of milk chocolate - Atik, Didem Sozeri; Boluk, Esra; Toker, Omer Said; Palabiyik, Ibrahim; Konar, Nevzat (ELSEVIER, 2020)
Emulsifiers are the components used in chocolate technology especially due to their effects on the flow behavior. The most common used emulsifiers are lecithin and polyglycerol polyricinoleate (PGPR). In this study, the effects of lecithin (0.25-0.500 g/100 g) and PGPR (0.00-0.25 g/100 g) usage on the rheological properties, texture (hardness, fracturability), formation of beta(v) polimorph and colour values of milk chocolate were studied by using Mixture Design technique. The ratio of lecithin:PGPR did not significantly affect color of milk chocolate, but yield stress and viscosity of samples were found to be statistically significantly affected (p < 0.05). Formation of beta(v) polimorph was found to induced by increasing lecithin content while decreasing PGPR. Fracturability and hardness increased with PGPR addition. The results of the present study indicated that lecithin:PGPR ratio in milk chocolate was important for crystallization behavior as well as processability of the inter-mediate products and the quality of the end-products.
Keywords: Chocolate; Emulsifier; Mixture design; Crystallization; Rheology; FAT BLOOM; RHEOLOGICAL PROPERTIES; MELTING PROPERTIES; PARTICLE-SIZE; TEMPERATURE; BEHAVIOR; SWEETENERS; Food Science & Technology